Proliferation dynamics of acute myeloid leukaemia and haematopoietic progenitors competing for bone marrow space - O. Akinduro (Nature Portfolio, 2018)
How leukaemia cells invade the bone marrow by outcompeting haematopoietic cells is still unclear. Here, the authors used detailed cell number measurements in conjunction with a dual pulse labelling method to determine proliferation rates and followed the in vivo dynamics of AML disease progression.